Characterization of diet in Biochemical and anthropometric profiles whit the analysis of main components in obese patients, Guayaquil – Ecuador: Caracterización de la dieta en los perfiles bioquímicos y antropométricos con análisis de componentes principales en pacientes obesos, Guayaquil – Ecuador - Gomez Rutti, Yuliana Yessy (2023)
Objectives: Determine the characterization of the diet in biochemical and anthropometric profiles with the analysis of the principal components in obese Ecuadorian patients. Methods: Descriptive, comparative, longitudinal studies; we had access to the institutional health clinical history database and a study group was formed, they were offered a low-carbohydrate diet. The sample consisted of 110 obese patients from the Hospital of Guayaquil-Ecuador. Results: The patients were between the ages of 25 to 65 years. The results showed a significant loss of BMI (kg/m2) (Δ-2,6±1.9) (p<0,001), waist circumference (cm) (Δ-5,1±4,7) (p<0,001), body fat (%) (Δ-3,6±3,6) (p<0,001), triglycerides (mg/dL) (Δ-25,4±72,9) (p<0,001) and glucose (mg/dL) (Δ-6,8±9,6) (p<0,001). Conclusion: The low carbohydrate diet reduces BMI, waist circumference, body fat, triglycerides and glucose in obese patients.